DNMT gene expression in peripheral leukocytes in schizophrenia and correlations with one-carbon metabolites: folate, total homocysteine, and vitamin B6 - Tomioka, Yukiko; Nakataki, Masahito; Umehara, Hidehiro; Yoshida, Tomohiro; Matsuda, Hiroya; Matsumoto, Yui; Aoki, Mariko; Yoshida, Yuri; Kamiyama, Yuichiro; Nakayama, Tomohiko; Yamada, Naoki; Numata, Shusuke (Frontiers in Psychiatry, 2026)
AimsPrevious studies have identified alterations in one-carbon metabolism (OCM), including DNA methylation abnormalities, in individuals with schizophrenia. However, the precise etiology of this disorder remains unclear. In the present study, we examined variations in the expression of DNMT1 and DNMT3a—genes implicated in DNA methylation—using peripheral blood leukocytes from Japanese patients with chronic schizophrenia and healthy controls. Additionally, using our previously acquired data, we explored the association between OCM-related factors and DNMT expression levels.MethodsExpression levels of DNMT1 and DNMT3a in 215 patients with chronic schizophrenia and 210 healthy controls were quantified using real-time PCR. The Mann-Whitney U test was used to compare the differences between two independent groups. Furthermore, Spearman’s correlation analysis was conducted to investigate the relationships between DNMT genes` expression levels and OCM-related metabolites (blood folate, vitamin B6, and total homocysteine).ResultsThe expression levels of DNMT1 and DNMT3a in peripheral leukocytes were significantly elevated in patients with chronic schizophrenia compared with controls (p = 1.4 × 10–6 and 2.9 × 10-3, respectively). DNMT1 mRNA expression levels exhibited a weak negative correlation with folate exclusively in the aggregated cohort (N = 425) (ρ = −0.16, adjusted q = 5.0 × 10-3), and DNMT3a mRNA expression levels showed a weak negative correlation with vitamin B6 alone in the combined group (ρ = −0.12, adjusted q = 0.03).ConclusionThese findings suggest a potential correlation between nutritional status and elevated expression of DNMT1 and DNMT3a in schizophrenia. Our findings contribute to the understanding of the epigenetic mechanisms associated with schizophrenia and highlight the need for further investigation of the relationships among gene expression, nutritional status, and psychiatric manifestations.